Cytotoxic Effect of Hederagenin on NCI-H460, Human Non-small Lung Cancer Cells and its Free Radical Scavenging Activities. Issue 5 (1st November 2016) - Oladimeji, Abdulkabir Oladele; Oladosu, Ibrahim Adebayo; Ali, Muhammad Shaiq; Khan, Salman Ahmed; Yousuf, Sammer
Abstract: Lung cancer is among the leading causes of death worldwide. Cytotoxic and free radical scavenging activities of anhydrous hederagenin, isolated from Cussonia arborea Hochst. ex A. Rich were evaluated on human NCI-H460 lung cancer cells, OHand DPPH. The structure was unambiguously deduced largely bysingle-crystal X-ray diffraction (XRD) analysis. The metabolite displayed significant cytotoxic activity (IC50 = 20.27 μg/mL). It scavenged hydroxyl radical by 90.2% and bleached purple color of DPPH (IC50 = 49.6 μg/mL) at 1.0 mg/mL.The crystal belongs to the orthorhombic space group P21, with unit cell parameters a = 12.2865(19) Å, b = 16.414(3) Å, c = 13.441(2) Å. Our findings suggest that hederagenin may have the potential to provide significant natural defense againsthuman lung cancer.